Hierarki Kepala Madrasah sebagai Inisiator Pengorganisasian Sumber Daya Manusia - Sugiarto, Rudi (Global Education Journal, 2023)
The purpose of this study was to find out the efforts of the madrasah head in organizing the human resources of MTs Darul Ulum. The research method uses a qualitative case study type approach. Data was collected through the process of observation, interviews with the head of the madrasa, Deputy Head of Curriculum, the madrasah committee, and one of the madrasah teachers, and documentation. Data were analyzed through the process of condensing data, presenting data, and drawing conclusions. While the source triangulation technique is a tool to measure the validity of the data. The results showed that the three organizing processes carried out by the head of the MTs Darul Ulum as the initiator showed a systematic and mechanical managerial process by adjusting the capabilities of the human resources they had. Among them, structuring (clear lines of organizational structure), assembling resources (organization of human resources according to organizational needs), and staffing (placement of human resources according to abilities and qualifications). Of course the head of MTs Darul Ulum is capable of being the initiator in a hierarchical order as a step in organizing quality organizational human resources.